Clinical Impact of Alcohol‐Related Cirrhosis in the Next Decade: Estimates Based on Current Epidemiological Trends in the United States. (25th October 2015) - Guirguis, John; Chhatwal, Jagpreet; Dasarathy, Jaividhya; Rivas, John; McMichael, David; Nagy, Laura E.; McCullough, Arthur J.; Dasarathy, Srinivasan
Abstract : Background: Identifying changes in the epidemiology of liver disease is critical for establishing healthcare priorities and allocating resources to develop therapies. The projected contribution of different etiologies toward development of cirrhosis in the United States was estimated based on current publications on epidemiological data and advances in therapy. Given the heterogeneity of published reports and the different perceptions that are not always reconcilable, a critical overview rather than a formal meta‐analysis of the existing data and projections for the next decade was performed. Methods: Data from the World Health Organization Global Status Report on Alcohol and Health of 2014, Scientific Registry of Transplant Recipients from 1999 to 2012, National Institute on Alcohol Abuse and Alcoholism, and the Centers for Disease Control and Prevention were inquired to determine future changes in the epidemiology of liver disease. Results: Alcohol consumption has increased over the past 60 years. In 2010, transplant‐related costs for liver recipients were the highest for hepatitis C (~$124 million) followed by alcohol‐related cirrhosis (~$86 million). We anticipate a significant reduction in incidence cirrhosis due to causes other than alcohol because of the availability of high efficiency antiviral agents for hepatitis C, universal and effective vaccination for hepatitis B, relative stabilization of the obesity trends in the United States, and novel, potentially effective therapies for nonalcoholic steatohepatitis. The proportion of alcohol‐related liver disease is therefore likely to increase in both the population as a whole and the liver transplant wait list. Conclusions: Alcohol‐related cirrhosis and alcohol‐related liver disorders will be the major cause of liver disease in the coming decades. There is an urgent need to allocate resources aimed toward understanding the pathogenesis of the disease and its complications so that effective therapies can be developed.